2020
DOI: 10.1021/acssuschemeng.0c05294
|View full text |Cite
|
Sign up to set email alerts
|

Facile Grafting of Imidazolium Salt in Covalent Organic Frameworks with Enhanced Catalytic Activity for CO2 Fixation and the Knoevenagel Reaction

Abstract: Ionic liquids (ILs) have gained significant attention in past decades due to their important characteristics and superior application potential. However, liquid nature is a big hindrance to the further development and applications of ILs. In this work, we report a simple acid−base neutralization strategy used to graft imidazolium salts into covalent organic frameworks (COFs) for the catalysis of CO 2 chemical fixation and the Knoevenagel condensation reaction. It is found that in comparison with liquid IL, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…Subsequently, another imidazolium salt‐modified porous COF‐HNU14 was synthesized by impregnating TpPa‐SO 3 (monomers: 1,3,5‐triformylphloroglucinol (Tp) and 2,5‐diaminobenzenesulfonic acid (Pa‐SO 3 H)) into the aqueous solution of H1‐aminopropyl‐3‐methylimidazolium bromide [APMIM][Br] for cycloaddition of CO 2 with epoxides ( Figure ). [ 42 ] Similarly, COF‐HNU14 performed excellent catalytic activity (96%) in comparison with [APMIM]Br IL (69%) under the catalytic reaction for propylene oxide and CO 2 . The improved catalytic performance was assigned to the nanoscale ordering of COF‐HUN14.…”
Section: Applications Of Cofs‐ils Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, another imidazolium salt‐modified porous COF‐HNU14 was synthesized by impregnating TpPa‐SO 3 (monomers: 1,3,5‐triformylphloroglucinol (Tp) and 2,5‐diaminobenzenesulfonic acid (Pa‐SO 3 H)) into the aqueous solution of H1‐aminopropyl‐3‐methylimidazolium bromide [APMIM][Br] for cycloaddition of CO 2 with epoxides ( Figure ). [ 42 ] Similarly, COF‐HNU14 performed excellent catalytic activity (96%) in comparison with [APMIM]Br IL (69%) under the catalytic reaction for propylene oxide and CO 2 . The improved catalytic performance was assigned to the nanoscale ordering of COF‐HUN14.…”
Section: Applications Of Cofs‐ils Compositesmentioning
confidence: 99%
“…In a word, the high effectivity, catalytic selectivity, and universality of COFs-ILs composites are beneficial to enrich the metal-free catalysts used for CO 2 conversion and other organic reactions. [42] Copyright 2020, American Chemical Society.…”
Section: Catalysismentioning
confidence: 99%
“…[1] The progress of synthetic chemistry has resulted in the construction of COFs with different structures for a variety of applications, including ion conduction, [2] catalysts, [3] gas storage and separation, [4] sensors, [5] energy storage and conversion. [6] In the past decades, COFs with different functionalities have been used as heterogeneous catalysts for many organic reactions, such as Suzuki-Miyaura coupling reaction, [7] Henry reaction, [8] Michael addition reaction, [9] Diels-Alder cycloaddition reaction, [10] epoxidation of alkenes, [11] addition of epoxides to CO 2 , [12] Knoevenagel reaction, [13] and a variety of tandem reactions. [14] Nitrogen-containing heterocycles are usually DOI: 10.1002/macp.202100462 important intermediates of pharmaceuticals and agrochemicals because of their various biological functions and properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, porous materials, e.g. MOFs (Huang et al, 2020), COFs (Zhao et al, 2020) and CMPs (Tantisriyanurak et al, 2020;Xu et al, 2021) have been demonstrated as promising platforms to develop recyclable heterogeneous catalysts in part due to their large specific surface areas which could accommodate abundant guest molecules and afford many nanoreactors. In particular, researchers have been actively studying CMP-based heterogeneous catalysts over the last decade due to their insolubility in common organic solvents, high stability, inherent porosity and tailor-made functionality through facile structural design.…”
Section: Introductionmentioning
confidence: 99%